STRATEGIES FOR IMPROVING TEACHER’S WORK ENTHUSIASM IN PUBLIC UNIVERSITIES IN GUANGXI - Shibin, Ye; Suteeniran, Niran; Dejhome, Pachara; Sawangcharoen , Kanakorn; Wimuttipanya, Jittawisut (Journal of MCU Nakhondhat, 2024)
The purpose of this research is to create a strategy for improving teachers’ work enthusiasm in public universities in Guangxi. People’s Republic of China Using a survey research design, the population included teachers at a public university in Guangxi. People’s Republic of China, 378 people, selected specifically The research tool is a 5-level estimation questionnaire with a confidence level of .96. Statistics for data analysis include percentages, means, and standard deviations. and content analysis The results of the research found that the improvement of teachers’ work enthusiasm in Guangxi State University was affected by salary. teacher honors stability in work Job promotion status and interpersonal relationships Teachers’ interpersonal relationships and prestige have the greatest impact on teachers’ work enthusiasm in Guangxi State Universities. Meanwhile, salary status and promotions have the least impact. Based on the actual situation of Guangxi State University, in the long term, it is necessary to explore a reasonable salary system. and setting standards for promotion in various positions that match teachers’ actual abilities and performance. This can stimulate teachers to increase their enthusiasm for work very well in the short term because the salary system and promotion standards cannot be changed. Teachers should be motivated to work actively by improving interpersonal relationships in the teacher environment. and increase the frequency and type of prestigious incentives. and rationalize job security so that teachers are willing to make long-term investments in their careers. and are ready in terms of knowledge and understanding operational skills and good attitude towards the organization.